The Contribution of Limb Muscle Explosive Power and Eye-Foot Coordination to Foot Ball Shooting Results for Physical Education Fkip Uir Students Class of 2021 Local C - Paisal Hamdani Malau; M. Fransazeli Makarohim (FKIP Universitas Islam Indragiri, 2023)
The purpose of this study was to determine the contribution of leg muscle explosive power and eye-foot coordination to the results of shooting footballs for local Physical Education Fkip uir students class of 2021 c. This type of research is correlation research. The population in this study were 16 students. Data collection techniques used in this study are observation, literature, tests and measurements. Data analysis technique uses multiple correlation. Based on the results of the study, which was proven by data analysis using correlation calculations, it can be concluded that, There is a significant relationship between Leg Muscle Power and Shooting with a tcount (1.971) < ttab (1.739). There is no significant relationship between eye-foot coordination and shooting with tcount (0.790) < ttable (1.739). There is a relationship between leg muscle power and eye-foot coordination with shooting football with tcount (2.147) < ttab (1.739).